Dimensionamento de pisos mistos em situação de incêndio com proteção apenas das vigas principais - Cristiane Carneiro Spindola (2002)
In steel buildings, it has been common to design floorslabs with composite beams and steel deck. Fire design, generally uses a traditional and conservative procedure, according to prestandard Eurocode 4: Part 1.2 (Design of Composite Steel and Concrete Structures - Structural Fire Design, 1994), and NBR 14323 (Dimensionamento de Estruturas de Aço de Edifício em Situação de Incêndio, 1999). Consequently, it's often necessary to protect the steel profile of the composite beam, with thermal insulating material, and to use positive additional reinforcement in the slab.This work, initially presents the design procedure theoretical basis, which was recently developed by English researches, considering beams and slab working together, allowing not using fire protection in secondary beams. In the sequence, are shown how these procedure can be applied to Brazilian reality, using Brazilian's products and design specifications, and are presented practical examples of design, that can observe the economy reached in the quantity of fire protection material. A plan of design was developed in order to make easy the obtaining of comparative results.